Immigrazione: la salute mentale come diritto di tutti - Carnevali, Rossella (Il sogno della farfalla, 2016)
Migrants are exposed to violations of human rights on an almost constant basis. This may cause greater vulnerability to psychiatric diseases. Italy’s inadequate migration policies increase this vulnerability and do not allow for people who are at greater risk to be identified. Literature reports socio-environmental factors amongst the main causes leading to the onset of mental diseases, including more severe ones. It is at this level that we can work on a preventive basis. Poor psychiatric education, from a scientific, cultural and human point of view, may lead to incorrect diagnosis and wrong therapies. Human Birth Theory enables psychiatrists to rid themselves of any prejudices against migrants and to recognise the right to diagnosis and treatment of mental diseases for everyone.